Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1115/1.3122782
|View full text |Cite
|
Sign up to set email alerts
|

Subcooled Pool Boiling in Variable Gravity Environments

Abstract: Virtually all data to date regarding parametric effects of gravity on pool boiling have been inferred from experiments performed in low-g, 1g, or 1.8g conditions. The current work is based on observations of boiling heat transfer obtained over a continuous range of gravity levels (0g–1.8g) under subcooled liquid conditions (n-perfluorohexane, ΔTsub=26°C, and 1 atm), two gas concentrations (220 ppm and 1216 ppm), and three heater sizes (full heater-7×7 mm2, half heater-7×3.5 mm2, and quarter heater-3.5×3.5 mm2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…Raj [5] found that if the gravitational acceleration is larger than 0.3 g e the heat fluxes for three heater sizes are similar. But for the acceleration values smaller than 0.3 g e , it is obvious that the heat transfer performance changes with the heater size.…”
Section: Introductionmentioning
confidence: 99%
“…Raj [5] found that if the gravitational acceleration is larger than 0.3 g e the heat fluxes for three heater sizes are similar. But for the acceleration values smaller than 0.3 g e , it is obvious that the heat transfer performance changes with the heater size.…”
Section: Introductionmentioning
confidence: 99%
“…The heater size effects were studied extensively by Kim et al [33,34]. According to their research, relative small heater size has poorer heat transfer than that of a large size.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, He et al [9] studied the non-uniformity of the temperature field in a closed cavity with centrifugal acceleration in simulations and experiments. On the other hand, extensive research focusing on microgravity [10][11][12] also introduced valuable data of the boiling flow in high gravity more or less. However, their mutual limitation is that the experiments are conducted in the on-board parabolic flight, so their maximum accelerations of 2 g is insufficient for manned or unmanned flight vehicles.…”
Section: Introductionmentioning
confidence: 98%